Analisis Manajemen Risiko Pada Perencanaan Bisnis PROPTECH: (Property Technology) - Sidiqurrohman, Dimas Satria; Syah, Tantri Yanuar Rahmat; Negoro, Dimas Angga; Iskandar, Muhammad Dafi (Indra Institute Research & Publication, 2024)
This study aims to analyze risk management in PropTech (Property Technology) business planning, which aims to integrate technology into the property sector to facilitate the process of searching, renting, and managing property. With increasing urbanization and housing needs, this sector faces various challenges, such as market fluctuations, government regulations, and demands for innovation. PropTech presents technology-based solutions to improve the efficiency and convenience of property rental services. To achieve business sustainability and reduce risks that hinder operations, the implementation of comprehensive risk management is essential. Risk management in PropTech follows the ISO 31000:2018 standard, including risk identification, analysis, evaluation, and mitigation through a holistic approach that considers internal and external risks. This study uses a qualitative approach with a case study method on the PropTech business platform through interviews and observations, and involves various stages of risk management, including periodic monitoring and evaluation to ensure the effectiveness of risk mitigation. The results of the study show the importance of implementing dynamic, structured, and inclusive risk management principles to maintain performance and competitiveness in the competitive property industry.